2017
DOI: 10.1111/imm.12722
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cell‐derived gamete‐associated proteins incite rejection of induced pluripotent stem cells in syngeneic mice

Abstract: The safety of induced pluripotent stem cells (iPSCs) in autologous recipients has been questioned after iPSCs, but not embryonic stem cells (ESCs), were reported to be rejected in syngeneic mice. This important topic has remained controversial because there has not been a mechanistic explanation for this phenomenon. Here, we hypothesize that iPSCs, but not ESCs, readily differentiate into gamete-forming cells that express meiotic antigens normally found in immune-privileged gonads. Because peripheral blood T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In contrast, others have reported that mouse and human iPSC derivatives can be immunogenic in syngeneic or AU recipients and in an AU humanized mouse model, respectively 68 . Interestingly, it has also been shown that a host immune response (T-cell infiltration) associated with necrosis following transplantation of syngeneic iPSC, appears to be dependent on the antigenic profile of the transplant 6,9 . Recently, the more economically sustainable “MHC-paradigm”, i.e., matching the major histocompatibility complex (MHC) of both donor and recipient 10 , was tested in NHPs using retinal 11 or dopaminergic transplants 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, others have reported that mouse and human iPSC derivatives can be immunogenic in syngeneic or AU recipients and in an AU humanized mouse model, respectively 68 . Interestingly, it has also been shown that a host immune response (T-cell infiltration) associated with necrosis following transplantation of syngeneic iPSC, appears to be dependent on the antigenic profile of the transplant 6,9 . Recently, the more economically sustainable “MHC-paradigm”, i.e., matching the major histocompatibility complex (MHC) of both donor and recipient 10 , was tested in NHPs using retinal 11 or dopaminergic transplants 12 .…”
Section: Introductionmentioning
confidence: 99%
“…During normal body function, different generations of cells must undergo processes that turn mature cells into stem cells ( 33 ). Although research relating to the induction of stem cells by acid has been questioned recently ( 34 ), there is no essential difference between the basic concept of this research and stem cell induction. The present study demonstrated that changes in the cellular environment may induce mature cells to become stem cells, although the identity of these specific environmental factors remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Different combinations of transcription factors, such as Oct4, Sox2, Nanog, and Lin28 (68) or only Oct4 and Sox2 (69) can be also used to generate iPSCs. Despite the controversy on immunogenicity of autologous iPSCs (70)(71)(72)(73), devoid of ethical issues qualifies them as one of the most promising cell sources for cardiac tissue engineering.…”
Section: Pluripotent Stem Cellsmentioning
confidence: 99%